2017
DOI: 10.1016/j.bandc.2017.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Response bias and response monitoring: Evidence from healthy older adults and patients with mild Alzheimer’s disease

Abstract: Patients with Alzheimer's disease (AD) often exhibit an abnormally liberal response bias in recognition memory tests, responding “old” more frequently than “new.” Investigations have shown patients can to shift to a more conservative response bias when given instructions. We examined if patients with mild AD could alter their response patterns when the ratio of old items is manipulated without explicit instruction. Healthy older adults and AD patients studied lists of words and then were tested in three old/ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
1
5
1
Order By: Relevance
“…There was also an interaction between group and stimulus condition with healthy older adults shifting to a more liberal response bias for the instrumental condition (the most difficult condition), whereas the patients with AD used a more liberal criterion for the spoken condition (the least difficult condition). Surprisingly, patients with AD did not show a more liberal response bias overall than healthy older adults, which is contrary to typical findings in prior studies (Budson, Wolk, Chong, & Waring, 2006;Deason et al, 2017;Snodgrass & Corwin, 1988). However, in our prior work (Simmons-Stern et al, 2012), patients with AD showed a more conservative response bias for the musically encoded items, suggesting that potentially music may encourage the use of a more stringent criterion, requiring a stronger memory trace to endorse an item as old.…”
Section: Discussioncontrasting
confidence: 99%
“…There was also an interaction between group and stimulus condition with healthy older adults shifting to a more liberal response bias for the instrumental condition (the most difficult condition), whereas the patients with AD used a more liberal criterion for the spoken condition (the least difficult condition). Surprisingly, patients with AD did not show a more liberal response bias overall than healthy older adults, which is contrary to typical findings in prior studies (Budson, Wolk, Chong, & Waring, 2006;Deason et al, 2017;Snodgrass & Corwin, 1988). However, in our prior work (Simmons-Stern et al, 2012), patients with AD showed a more conservative response bias for the musically encoded items, suggesting that potentially music may encourage the use of a more stringent criterion, requiring a stronger memory trace to endorse an item as old.…”
Section: Discussioncontrasting
confidence: 99%
“…This study attempted to further illuminate neural mechanisms underlying the maintenance of a conservative decision criterion during recognition memory. Patients with damaged and/or dysfunction frontal lobes oftentimes establish overly liberal decision criteria when making recognition judgments (Biesbroek et al, 2015 ; Deason et al, 2017 ). In healthy individuals, widespread fronto-parietal BOLD activity is present in the H > CR contrast of recognition memory tests when maintaining a conservative decision criterion, but not a liberal criterion (Aminoff et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with frontal lobe lesions tend to establish more liberal decision criteria as evidenced by increased false alarm rates during recognition memory (Parkin et al, 1996 ; Schacter et al, 1996 ; Swick and Knight, 1999 ; Verfaellie et al, 2004 ; Callahan et al, 2011 ; Biesbroek et al, 2015 ). A tendency to set liberal decision criteria is also observed in other patient populations associated with frontal lobe damage or dysfunction, including Alzheimer's disease (Budson et al, 2006 ; Waring et al, 2008 ; Beth et al, 2009 ; Deason et al, 2017 ) and schizophrenia (Moritz et al, 2008 ). Prefrontal cortex processes can also be disrupted through drug administration, such as with Δ 9-tetrahydrocannabinol (THC) (Bossong et al, 2012 ), which demonstrated increased false alarm rates during recognition memory (Doss et al, 2018 ).…”
Section: Introductionmentioning
confidence: 98%
“…Conservative responding is a memory heuristic in which a participant endorses an item as previously encountered only if they are certain of their decision (Waring, Chong, Wolk, & Budson, 2008). Conservative responding has been found to reduce the degree of false recognition in word list paradigms by shifting the metamemorial information that participants employ when making memory decisions (Deason et al, 2017;Waring et al, 2008). Use of conservative responding has also been found to shift the response criterion of participants with Alzheimer's disease, although it has not previously been found to meaningfully improve their discrimination of true and false information (Deason et al, 2017;Waring et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Conservative responding has been found to reduce the degree of false recognition in word list paradigms by shifting the metamemorial information that participants employ when making memory decisions (Deason et al, 2017;Waring et al, 2008). Use of conservative responding has also been found to shift the response criterion of participants with Alzheimer's disease, although it has not previously been found to meaningfully improve their discrimination of true and false information (Deason et al, 2017;Waring et al, 2008). Although healthy older controls and participants with mild cognitive impairment due to Alzheimer's disease have been found to apply cognitive strategies to reduce false memory in categorized list paradigms (Brueckner & Moritz, 2009;Deason et al, 2017;Tat et al, 2016), individuals with Alzheimer's disease dementia have been found to either be ineffective or inconsistent in their application of cognitive strategies (Abe et al, 2011;Budson, Dodson, Daffner, & Schacter, 2005;Pierce, Waring, Schacter, & Budson, 2008).…”
Section: Introductionmentioning
confidence: 99%